X-ray phase contrast for intra-operative specimen imaging in breast conserving surgery and other areas - Olivo, Alessandro; Leff, Daniel R. (Frontiers in Medical Engineering, 2025)
Current platforms for cancer surgery are inherently imprecise and this is manifest in high rates of incomplete excision and reoperative intervention. A prominent example is breast conserving surgery where intra-operative determination of margin involvement is challenging leading to high national average rates of positive resection margins needing revisional procedures. To meet these demands of improved precision it is valuable to image the resected tissue in real time in such a way that enables tissue characterization. A plethora of imaging methods have been proposed, with X-ray micro-CT appearing as one of the most promising due to its ability to scan the entire resection in 3D, as opposed to 2D imaging methods and/or approaches that only allow sampling the tissue at specific locations with limited field-of-view. A key, well-known limitation is the limited soft tissue sensitivity of X-rays, which has recently been overcome through the advent of X-ray phase contrast imaging (XPCI). The introduction of XPCI methods working with conventional sources (as opposed to specialized facilities such as synchrotrons) has spawn a series of exciting studies aiming at translating XPCI into clinical applications, which have recently extended into the realm of intra-operative imaging for breast conserving surgery and other areas. This article briefly introduces the XPCI technology, then reviews its existing applications in intra-operative imaging.